AI for Self-Study in Interpreting. Supporting Practice Design and Feedback in Dialogue Interpreting. - Varela-Salinas, María José (My University, 2025)
This seminar explores how interpreting students can use AI tools to design effective self-study routines for oral skills. Rather than focusing on a specific mode, the session views interpreting as a cluster of skills and shows how AI can support their development. The seminar is aimed at interpreting students at different stages of their training, but will also be relevant to students who simply wish to improve their oral production and comprehension in one or more working languages.
Conferencia dada en la Università degli Studi Internazionali de Roma.
Keywords: Inteligencia artificial - Aplicaciones pedagógicas; Interpretación; Inteligencia Artificial; IA; Práctica de la interpretación